2016
DOI: 10.1016/j.crpv.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural features of the femur in early ophiacodontids: A reappraisal of ancestral habitat use and lifestyle of amniotes

Abstract: a b s t r a c tOphiacodontids have long been considered the basalmost synapsids, and to have retained a fairly aquatic, piscivorous lifestyle typical of stem-amniotes. A restudy of their bone histology and microanatomy shows that Clepsydrops collettii, a Late Carboniferous ophiacodontid, has a thin, compact cortex and lacks a medullary spongiosa, two features that suggest a truly terrestrial lifestyle. The Early Permian Ophiacodon uniformis has a thicker cortex with a few resorption cavities and bone trabecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 46 publications
(73 reference statements)
4
29
0
Order By: Relevance
“…Ophiacodon also resembles the terrestrial type (like Varanus salvator or V. rudicollis) in having the cervical vertebrae longer than the dorsals and the caudals, and the dorsals are also longer than the caudals. This is congruent with the latest bone microanatomical study (Laurin and de Buffrénil, 2016). However, this interpretation should be treated with caution because we did not study the specimens directly and there could be some distortion due to incompleteness of the available specimens plotted, a condition that is reflected in their noisy profile (Figure 11H).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Ophiacodon also resembles the terrestrial type (like Varanus salvator or V. rudicollis) in having the cervical vertebrae longer than the dorsals and the caudals, and the dorsals are also longer than the caudals. This is congruent with the latest bone microanatomical study (Laurin and de Buffrénil, 2016). However, this interpretation should be treated with caution because we did not study the specimens directly and there could be some distortion due to incompleteness of the available specimens plotted, a condition that is reflected in their noisy profile (Figure 11H).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, another work that inquired into the lifestyle of Ophiacodon through a study of bone microanatomy (Germain and Laurin, 2005) found evidence supporting a semi-aquatic to terrestrial pattern. However, a more recent study (Laurin and de Buffrénil, 2016) concluded (based on another bone section) that this basal synapsid may have been terrestrial and that this may reflect the early amniote condition because an older basal synapsid (Clepsydrops collettii) exhibited a microanatomical signature typical of terrestrial tetrapods. However, this could also reflect the condition in early synapsids.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The local strain at the trabeculae connections enables to ensure a better distribution of the contact pressure [12], [13]. This structure meets a variety of specifications and have been adapted to the lifestyle of each living species [14], [15], [16].…”
Section: Bio-inspired Optimization Methodsmentioning
confidence: 99%
“…Different sampling planes thus may intersect a variable microstructure of the medullary region; the density of trabeculae increases proximally and distally together with decreasing cortical bone thickness. Laurin and Buffrénil (2015) documented the misinterpretation of lifestyle based on the microstructural features of Ophiacodon because the section plane was not precisely mid-diaphyseal. However, the specimens from Briar Creek Bonebed varied not only on the microstructural level, but also represent the different histology (growth pattern, tissue type, vascularization pattern), suggesting that the plane of section cannot explain all of the observed variability.…”
Section: The Origin Of the Variabilitymentioning
confidence: 99%